Country-specific challenges to improving effectiveness, scalability and sustainability of agricultural climate services in Africa - Hansen, James W.; Born, Lorna; Dossou-Yovo, Elliott R.; Mwongera, Caroline; Dalaa, Mustapha A.; Tahidu, Osman; Whitbread, Anthony M.; Solomon, Dawit; Zougmore, Robert; Zebiak, Stephen E.; Dinku, Tufa; Grossi, Amanda (Frontiers in Climate, 2022)
Climate services are playing an increasing role in efforts to build the resilience of African agriculture to a variable and changing climate. Efforts to improve the contribution of climate services to agriculture must contend with substantial differences in national agricultural climate services landscapes. Context-specific factors influence the effectiveness, scalability and sustainability of agricultural climate service, but in ways that are challenging to anticipate. In the context of six countries (Ethiopia, Ghana, Kenya, Mali, Senegal, Zambia), this paper addresses the need to consider differing national contexts when developing strategies to make agricultural climate services in sub-Saharan Africa more effective, scalable and sustainable. Based on authors’ collective firsthand knowledge and a review of information from secondary sources, we identify key strengths and weaknesses of climate services relative to agriculture sector needs in the focus countries; and assess factors that have contributed to those differences. Focus countries differ substantially in areas such as the degree of public support, alignment of services with agricultural needs, service delivery channels, degree of decentralization, and public – private-sector balance. These differences have been driven largely by differing national policies, delivery capacity and external actors, but not by responsiveness to agricultural sector demands. Building on the analyses of country differences and their drivers, we then discuss four key opportunities to further strengthen the contribution of climate services to agriculture: (a) leveraging farmer demand to drive scaling and sustainability; (b) exploiting digital innovation within a diverse delivery strategy; (c) balancing public and private sector comparative advantage; and (d) embedding climate services in agricultural extension. For each of these opportunities, we consider how different country contexts can impact the potential effectiveness, scalability and sustainability of services; and how efforts to strengthen those services can account for context-specific drivers to manage the tradeoffs among effectiveness, scalability and sustainability.